New design of electrostatic mirror actuators for application in high-precision interferometry. (19th August 2015) - Wittel, H; Hild, S; Bergmann, G; Danzmann, K; Strain, K A
Abstract: We describe a new geometry for electrostatic actuators to be used in sensitive laser interferometers, suited for prototype and table top experiments related to gravitational wave detection with mirrors of 100 g or less. The arrangement consists of two plates at the sides of the mirror (test mass), and therefore does not reduce its clear aperture as a conventional electrostatic drive (ESD) would do. Using the sample case of the AEI-10 m prototype interferometer, we investigate the actuation range and the influence of the relative misalignment of the ESD plates with respect to the test mass. We find that in the case of the AEI-10 m prototype interferometer, this new kind of ESD could provide a range of 0.28 μ m when operated at a voltage of 1 kV. In addition, the geometry presented is shown to provide a reduction factor of about 100 in the magnitude of the actuator motion coupling to the test mass displacement. We show that therefore in the specific case of the AEI-10 m interferometer, it is possible to mount the ESD actuators directly on the optical table without spoiling the seismic isolation performance of the triple stage suspension of the main test masses.